FRI0376 EFFECT OF CARBAMYLATED LOW-DENSITY LIPOPROTEINS ON BONE CELLS HOMEOSTASIS. (2nd June 2020) - Lucchino, B.; Leopizzi, M.; Colasanti, T.; DI Maio, V.; Alessandri, C.; Valesini, G.; Conti, F.; DI Franco, M.; Spinelli, F. R.
Abstract : Background: Carbamylation is a post-translational modification occurring under several conditions such as uremia, smoking and chronic inflammation as in rheumatoid arthritis (RA). Low-density lipoproteins (LDL) represent a target of carbamylation. Carbamylated-LDL (cLDL) have an increased inflammatory and atherogenic potential. Growing evidence supports an influence of modified lipids on bone cells homeostasis. However, the role of cLDL on bone cells physiology is still unknown. Objectives: Considering the rate of carbamylation and the role of anti-carbamylated proteins antibodies as markers of erosive disease in RA, the purpose of this study is to investigate the effect of cLDL on bone homeostasis. Methods: In-vitro carbamylation of LDL was performed as previously described by Ok et al. (Kidney Int. 2005). Briefly, native LDL (nLDL) were treated with potassium cyanate (KOCN) for 4 hours, followed by excessive dialysis for 36 hours to remove KOCN. Both osteoclasts (OCs) and osteoblasts (OBLs) were treated at baseline with 20 μg/ml, 100 μg/ml and 200 μg/ml of cLDL or nLDL. To induce osteoclast differentiation, CD14+ monocytes were isolated from peripheral blood of healthy donors by magnetic microbeads separation and then cultured on a 96-wells plate in DMEM media supplemented with RANKL and M-CSF. After 10 days cells were fixed, stained for tartrate-resistant acid phosphatase (TRAP), a marker of OC differentiation, and counted. OBLs were isolated from bone specimens of 3 patients who had undergone to knee or hip arthroplasty for osteoarthritis and treated for 5 days with different concentrations of cLDL and nLDL. OBLs were fixed and stained for alkaline phosphatase positive activity (ALP), a marker of osteogenic differentiation. Total RNA was extracted from cell lysates. Copies of single-stranded complementary DNA (cDNA) were synthesized and analyzed by real-time PCR to evaluate RANKL and Osteoprotegerin (OPG) mRNA expression levels. Results: In OCLs culture, cLDL significantly decreased the number of OC compared to untreated cells (200 μg/ml p=0, 0015) and nLDL treated cells (200 μg/ml p= 0, 011; 20 μg/ml p= 0, 0014) (Fig 1 ). Moreover, treatment with cLDL induced an increase of not terminally differentiated OCs, reduced dimensions of OCs, less intense TRAP staining and vacuolization (Fig 2 ). In OBLs culture, cLDL (20, 100 μg/ml) significantly reduced the ALP activity of OBLs compared with untreated cells (p<0.05) (Fig 3 ). nLDL did not affect the ALP expression. Treatment with cLDL stimulated RANKL mRNA expression in osteoblasts increasing the RANKL/OPG ratio (Fig 4 ). Conclusion: cLDL induce a significant depression of OC and OBL differentiation. Moreover, cLDL increase RANKL expression in OBL, unbalancing bone tissue turnover towards bone resorption. Accordingly, cLDL could be implicated in the bone loss characterizing several conditions associated to an increased carbamylation, such as RA Disclosure of Interests: Bruno Lucchino: None declared, Martina Leopizzi: None declared, Tania Colasanti: None declared, Valeria Di Maio: None declared, cristiano alessandri Grant/research support from: Pfizer, Guido Valesini: None declared, fabrizio conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi, Manuela Di Franco: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Consultant of: Novartis, Gilead, Lilly, Sanofi, Celgene, Speakers bureau: Lilly